Condition Monitoring of Outdoor High Voltage Insulators, Online and Offline Techniques: A review - Haseeb Faisal; Arshad Ali; Muhammad Riaz (NUST Journal of Engineering Sciences, 2021)
Outdoor insulator plays a vital role in high voltage transmission and distribution system. The performance and properties of outdoor insulator may severely affect due to various types of pollutants. The failure of insulation in high voltage system results in loss of supply and a huge loss of electrical energy to distribution utilities. In order to reduce power losses and provide a reliable power transmission, selection and design of insulators is very important. To monitor the condition and performance of outdoor insulator in contaminated conditions an appropriate diagnostic technique is required. In this paper various online and offline techniques for conditioning monitoring of outdoor insulators are reviewed under different contaminated conditions. To maintain the healthy environment, the condition monitoring of power line insulators is an important requirement. There are number of techniques that have been introduced to fulfil this requirement. Each technique used at different contaminated condition have their own pros and cons. The findings indicate that the most important effect on the surface of the insulators based on the contamination on the surface leakage current and the flashover voltage. This paper will help in the selection and design of condition monitoring techniques for high voltage outdoor insulator.